ANALISIS HASIL BELAJAR SISWA DENGAN MENGGUNAKAN MEDIA PEMBELAJARAN BERBASIS WORDWALL DI SEKOLAH DASAR - Alma Nur Azizzah; Neni Nadiroti Muslihah; Fitri Ayu Febrianti; Ejen Jaenal Mutaqin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
In this modern era of education, teachers must be able to create a safe, comfortable, and conducive learning environment to achieve maximum learning outcomes. Therefore, teachers must be innovative and creative in teaching and learning activities, using learning media that are engaging, interactive, enjoyable, effective, and meaningful for students. The learning media used is a wordwall, which provides various types of educational games, including quizzes, crosswords, open the box, and so on. The goal is to analyze the relationship between wordwall application use and student learning outcomes. The methods used are observation and literature review, analyzing relevant research from journals, articles, and other sources. The results of the study indicate that wordwalls can increase learning motivation and student engagement in the learning process. The conclusion of this study states that wordwalls are a learning medium that can help elementary school teachers and students achieve better learning outcomes.